On the bright side, I'm now the girlfriend of a sex god : further confessions of Georgia Nicolson - Rennison, Louise (New York : HarperCollins, 2001)
Fourteen-year-old Georgia continues her diary in which she records her misadventures trying to reclaim the attention of seventeen-year-old Robbie, while coping with her friends, family, and dog-like cat Angus at the same time.
Sequel to: Angus, thongs, and full-frontal snogging.
Young Adult
Young Adult
School Library Journal
Booklist starred
Book Report starred
Keywords: Dating (Social customs) -- Fiction; Best Friends -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Family life -- England -- Fiction; England -- Fiction; Humorous stories; Dating (Social customs) -- Fiction; Friendship -- Fiction; Diaries -- Fiction; Family life -- England -- Fiction; England -- Fiction; Humorous fiction